2014
DOI: 10.1188/14.cjon.s3.17-25
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Interventions for Cancer- and Treatment-Related Cognitive Impairment

Abstract: Cancer- and cancer treatment-related cognitive impairment is a common, bothersome, and potentially debilitating symptom incurred by cancer survivors. Cognitive impairment has a significant impact on patients' day-to-day functioning and quality of life, but it remains under-recognized and undertreated. This article, which is an update from the initial Oncology Nursing Society Putting Evidence Into Practice for cancer- and cancer treatment-related cognitive impairment, provides a comprehensive critical review an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 85 publications
(167 reference statements)
0
30
0
Order By: Relevance
“…In addition, the development or application of appropriate interventions to ameliorate cognitive impairments and neurobehavioral symptoms are warranted. Numerous potential interventions have been examined so far, including cognitive rehabilitation (both compensatory approaches and computerized cognitive training), meditation, exercise, neuromodulation, and pharmacologic agents, but further research is still required as findings continue to be preliminary and limited to few cancer populations, most commonly breast cancer (Von Ah, Jansen, & Allen, 2014; J. S. Wefel, Kesler, Noll, & Schagen, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the development or application of appropriate interventions to ameliorate cognitive impairments and neurobehavioral symptoms are warranted. Numerous potential interventions have been examined so far, including cognitive rehabilitation (both compensatory approaches and computerized cognitive training), meditation, exercise, neuromodulation, and pharmacologic agents, but further research is still required as findings continue to be preliminary and limited to few cancer populations, most commonly breast cancer (Von Ah, Jansen, & Allen, 2014; J. S. Wefel, Kesler, Noll, & Schagen, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, an internet‐based Problem‐Solving Therapy intervention for depression did not demonstrate any significant effects. Although cognitive rehabilitation and Boswellia serrata did not demonstrate positive effects on HRQoL, they did have positive effects on cognitive impairment (see Von Ah et al for a review of evidence‐based interventions for cancer‐ and treatment‐related cognitive impairment; additionally, see Khan et al for a review of multidisciplinary interventions for brain tumor patients) and cerebral edema, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although CRCI is a potentially debilitating symptom for cancer survivors, few intervention trials have been conducted to address this symptom [13]. The newly released Survivorship Guidelines from the National Comprehensive Cancer Network (NCCN) recommend stress reduction and optimized management of other symptoms, including fatigue, pain, depression, and sleep disturbance, as general strategies to address CRCI [45]; however, no further information is provided.…”
Section: Discussionmentioning
confidence: 99%
“…Despite CRCI’s prevalence, few interventions targeting this symptom have been evaluated [13]. A number of interventional studies have shown promise in reducing the stress associated with CRCI [11]; however, few have directly addressed CRCI itself.…”
Section: Introductionmentioning
confidence: 99%